Togo Decentralized Service Delivery : Status and Way Forward for Strengthening Communes - World Bank Group (World Bank, Washington, DC, 2019)
This policy note constitutes an integral part of the policy dialogue with the Government of Togo in support of its ongoing decentralization process. The note recognizes the potential of decentralization to enhance local service delivery, if done well. Hence, the policy note assesses the current state of decentralization in Togo, with a specific focus on decentralization from central government to communes, the lowest level of government, and front-line for local service delivery. The note provides a set of recommendations for reform actions that can be implemented in short, medium, and long-term that will place the Togolese decentralization process and intergovernmental system on an optimal path, given the status of reforms as of the date of preparation of the policy note. This policy note is of equal importance for subnational stakeholders such as the prefects, and the special delegates, as well as the Secretaries-General of communes and other core staff. Finally, it will be of use to citizens, and to civil society organizations involved in initiatives to improve the delivery of communal services, as well as to the range of donors that are actively working to support the decentralization process in Togo.